2014
DOI: 10.1111/pce.12325
|View full text |Cite
|
Sign up to set email alerts
|

Implications of the mesophyll conductance to CO2 for photosynthesis and water‐use efficiency during long‐term water stress and recovery in two contrasting Eucalyptus species

Abstract: Water stress (WS) slows growth and photosynthesis (A(n)), but most knowledge comes from short-time studies that do not account for longer term acclimation processes that are especially relevant in tree species. Using two Eucalyptus species that contrast in drought tolerance, we induced moderate and severe water deficits by withholding water until stomatal conductance (g(sw)) decreased to two pre-defined values for 24 d, WS was maintained at the target g(sw) for 29 d and then plants were re-watered. Additionall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
83
2
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(93 citation statements)
references
References 105 publications
5
83
2
1
Order By: Relevance
“…Leaf sugar concentration has previously been associated with increasing NSLs in some trees and herbaceous plants, both in C 3 and C 4 metabolism (e.g. Jeannette et al , ; Turnbull et al , ; Franck et al , ; Hüve et al , ; Quentin et al , ; Cano et al , ; Ramalho et al , ; Kitao et al , ). This sugar‐mediated repression of photosynthesis is also consistent with earlier studies showing that decreasing sink strength limits photosynthetic efficiency (Azcón‐Bieto, ; Goldschmidt & Huber, ; Nakano et al , ; Hölttä et al , ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Leaf sugar concentration has previously been associated with increasing NSLs in some trees and herbaceous plants, both in C 3 and C 4 metabolism (e.g. Jeannette et al , ; Turnbull et al , ; Franck et al , ; Hüve et al , ; Quentin et al , ; Cano et al , ; Ramalho et al , ; Kitao et al , ). This sugar‐mediated repression of photosynthesis is also consistent with earlier studies showing that decreasing sink strength limits photosynthetic efficiency (Azcón‐Bieto, ; Goldschmidt & Huber, ; Nakano et al , ; Hölttä et al , ).…”
Section: Discussionmentioning
confidence: 98%
“…According to this hypothesis, as stomatal conductance g s increases (under constant environmental conditions) there is a trade‐off between increases in A through increased leaf‐intercellular CO 2 concentration c i , and decreases in A through NSLs associated with decreased leaf water potential (Dewar et al , ) and/or an associated increase in leaf sugar concentration (a potential mechanism is presented in Box 1), as observed in numerous species (e.g. Jeannette et al , ; Turnbull et al , ; Franck et al , ; Hüve et al , ; Quentin et al , ; Cano et al , ; Kelly et al , ; Ramalho et al , ; Kitao et al , ; Hölttä et al , ). As a result, there is a maximum in the A – g s curve at which stomatal limitations and NSLs to photosynthesis are in balance.…”
Section: Introductionmentioning
confidence: 99%
“…Drought can also lead to biochemical limitations of photosynthesis, but there is currently no clear trend in how plants will respond to limited water availability. Prior research has found mixed results; some studies indicating that drought decreases both V cmax and J max (Albert, Mikkelsen, Michelsen, Ro‐Poulsen, & Linden, ; Ge et al, ; Pena‐Rojas, Aranda, & Fleck, ; Yu, Chen, Xu, & Huang, ), some showing that V cmax and J max are not affected by drought (Cano, López, & Warren, ; Galle, Florez‐Sarasa, Aououad, & Flexas, ; Gu, Yin, Stomph, Wang, & Struik, ; Kelly, Duursma, Atwell, Tissue, & Medlyn, ; Turnbull et al, ), and others showing that drought caused an increase in J max while V cmax remained unchanged (Mokotedi, ). Martin‐St.Paul et al () grew plants in both wet and dry conditions and showed that J max and V cmax both decrease with subsequent soil drying, but this decline was steeper for plants grown in wetter conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that drought decreases g s (Flexas et al , Galmés et al ) and g m (Flexas et al , , Galmés et al , Cano et al , ). The decline of A N is mainly explained by the decrease in g s and g m under drought (Flexas et al , Galmés et al ), which is consistent with our results (see Fig.…”
Section: Resultsmentioning
confidence: 99%